Relationship of nutrient intakes and bone mineral density of elderly women in Daegu, Korea - Choi, Mi-Ja (The Korean Nutrition Society and the Korean Society of Community Nutrition, 2007)
The purpose of this study was to examine the relationship between nutrient intake and bone mineral density (BMD) of elderly women in Daegu, Korea. In this study, the bone mineral densities of 101 elderly women in Daegu were measured, and their nutrient intake, dietary habits, and maternal factors were determined through a survey. The subjects were divided into the normal group, the osteopenia group, and osteoporosis group to find out if there is a correlation between bone mineral density and maternal factors, dietary habits, and nutrient intake through their T-scores, analyzed according to the standards of WHO. Classification by T-scores of the participants were the normal group 25.7%, the osteopenia group 39.6%, the osteoporosis group 34.7%. Menopause age of the osteoporosis group was lower, postmenopausal period was longer, and last delivery age was significantly higher than the normal group (p<0.05). Osteoporosis group had a lower percentage of 'everyday' fruit and vegetable intakes and higher percentage of 'never' dairy intake than of the normal group. Vitamin A, vitamin B(1), and vitamin B(2) intakes of participants in the osteoporosis group were lower than those in the normal group (p<0.05). In conclusion, nutritional education is necessary to encourage high intake of milk and vegetables and fruits along with calcium, vitamin A, B(1), and B(1) intakes and low intake of sodium for the prevention of elderly women's osteoporosis.